Pengaruh Penggunaan Game Edukasi Terhadap Motivasi Belajar Siswa Kelas XI di SMA Negeri 1 Kabun - Lisnaini, Winda; Hendri, Nofri; Novrianti, Novrianti; Anugrah, Septriyan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The learning carried out at SMA Negeri 1 Kabun is known that the learning motivation of students is still low, this is due to the large number of students who have low motivation to learn, and teachers still use conventional media so that learning is less effective. This study aims to find out how much educational games affect the learning motivation of grade XI students in high school. This type of research is a quantitative approach in the form of Quasy Experiment with a type of nonequivalent control group design. The data collection technique used is a questionnaire. The data analysis techniques are normality test, homogeneous test, and hypothesis test with an independent test method of t-test samples. Where there were 70 students as a sample in class XI consisting of 35 people in the experimental class and 35 people in the control class. The results of the study showed that the use of educational games influenced the learning motivation of grade XI students, as evidenced by the sig value (2-tailed) which was 0.000, the value was less than 0.05 and the average score of the experimental class was higher than the average score of the control class, which was 87.97 > 69.69. From the hypothesis test that has been carried out, it can be concluded that the hypothesis Ha was accepted, and Ho was rejected, namely the Influence of Educational Games on Class XI Learning Motivation at SMA Negeri 1 Kabun